Urgensi Pembelajaran Bahasa Arab Dalam Pendidikan Islam - Vidya Isma Aulia; Wulan Anggraeni (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2023)
Islamic education itself is not spared from texts that speak Arabic either a little or a lot. Because Islam itself is the source of its teachings using Arabic. Therefore in this writing it is focused on the urgency of learning Arabic in Islamic education. The method used in this writing is qualitative with literature review. Where the discussion of this writing does not depend on the data but on the references used. Then the results of this writing show that one can understand several entitasals such as fiqh, the Koran and Alhadith, moral beliefs, and the history of Islamic civilization which are always used in the Al-Qur'an and hadith as a source of knowledge in each of these fields of knowledge. Arabic is a language that has the height of literary knowledge.